Oral Presentations Abstracts: CO-CREATION: A NOVEL APPROACH TO DEVELOPING GUIDELINES FOR RESEARCH INTEGRITY POLICY – LESSONS LEARNED FROM THE SOPS4RI PROJECT - LABIB, Krishma; TIJDINK, Joeri (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Co-creation is a qualitative research methodology that engages stakeholders in playful activities to produce user-centered outputs. Through an interactive and open approach, co-creation explores stakeholders’ latent values, generates innovative ideas, and captures minority views, allowing for in-depth understanding of how stakeholders are affected by various factors. Therefore, co-creation is a promising methodology for developing guidelines on research integrity (RI), although there is no literature available about co-creation in this context. In our presentation, we share experiences of using co-creation to design institutional guidelines on RI together with research managers, funders and researchers across Europe. We conducted 24 co-creation workshops on topics ranging from RI education, to creating a responsible research environment, resulting in concrete guidelines that research institutions and funders can implement to foster RI. Our experience has provided us with valuable insights on using co-creation for RI guideline development. While motivating research stakeholders – often serious and analytically oriented people – to engage in creative exercises can be a challenge, particularly in the online setting, it is possible to achieve when ‘play’ and ‘work’ are carefully balanced. Additionally, to ensure the concreteness of guidelines while accounting for differences among institutions and countries, best practice examples can be used to show different approaches to implementing more general guidance. We have also learned that it is valuable to explore stakeholders’ preferences regarding the guideline format, since implementability is not only influenced by the content. These insights provide practical considerations that other researchers can use when co-creating RI guidelines.